Analisis Tentang Pola Asuh Anak Dalam Perspektif Al-Qur’an Surah Luqman Ayat 13-19 - Raju Pratama Marronis; Salsa Bila Khotrun Nada; Layli Sartika; Puja Hayati; Wismanto Wismanto (STIKes Ibnu Sina Ajibarang, 2024)
Islamic education is depicted in the verses of QS. Luqman 13-19 of the Al-Qur'an provides answers to various aspects of educational problems faced by people today, including morals and worship. The aim of this research is to examine and analyze verses from the Koran relating to the concept of child care and its practice in the family. The research method used in this research is a qualitative study through a literature review using Maudhui's interpretive approach. The research concluded that the Koran has six terms related to children, including ghulam, walad, zurriya, ibn, tihr, and shabiy, each of which correlates with the concept of parenting. This parenting concept states that raising children is a responsibility parent.